Sustainable Hydrogen Production through Steam Methane Reforming and Water Electrolysis – A Review - William Mulewa , Mwadhi; Joseph Mbothu , Machandi; Elvis Makonde , Fwedeha (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Nearly half of the hydrogen produced worldwide comes from the most popular and economical method of hydrogen synthesis, methane steam reforming (MSR). However, there are a number of challenges that must be conquered before MSR can be widely used, despite the fact that it is a well-established technique. The primary research gaps in the MSR process center around improving the catalyst longevity and efficiency, addressing the process’s high energy consumption and carbon emissions, and enabling cost-effective small-scale hydrogen production. As an alternative, electrolysis of water could yield pure hydrogen. Nevertheless, hydrogen production from water electrolysis is synonymous with high costs (electricity, capital), as well as obstacles like the synthesis of more affordable and effective catalysts for the procedure, enhancing system intergration with renewables, and achieving true large scale manufacturing and scalability. In this review paper, both processes have been critically analyzed to give insights into current processes, the challenges faced, and prospects. Since both methane steam reforming and water electrolysis generate valuable hydrogen, optimization of the two could offer a more sustainable and reliable source of energy.